Acoustic approach of weldability for nanocomposite (nanosilica/PA6) welded by ultrasonic welding - Anderson Ribeiro; Jaime Casanova; Sérgio Duarte Brandi; Diego de Moura Pinheiro (Polímeros, 2020)
Abstract Polymer matrix nanocomposites (NMP) have attracted a great interest mainly in the automotive, aerospace and medical industries since they have good mechanical properties, dimensional, thermal and chemical stability, as well as interesting electrical conductivity and cost reduction in the manufacturing process. However, welding of this class of materials presents serious challenges such as improving weldability of the joint and understanding the mechanisms responsible for coalescence. The objective of this work was to evaluate the coalescence of an NMP joint (comprising a PA6 matrix and with nanosilica of different percentages of silicon) using ultrasonic welding, as well as to perform an acoustic approach of the energy dissipation during the welding process. It is concluded that the NMP samples tend to show better coalescence as the percentage of nanosilica increases, up to a certain limit. On the other hand, the higher the content of nanoparticle the smaller the energy absorption.